Comparative Analysis of (will, would and shall with khâh) in English and Persian (Eurasian Journal of Learning and Academic Teaching, 2022)
This Article focuses on analyzing Simple future tense making English modal verbs will/would and shall in comparison with Persian model verb khâh. They applied to mark future happening action in both Languages. In English, would is known as the past form of will and shall is mostly used in first person. All considered as equal to Persian verb khâh. This study covers grammatical and Structural comparison of these verbs. The required examples are taken from English-Persian translation books in order to examining whether English modal verbs are properly construed into Persian or not. The intended areas which are included into the scope of this study are grammatical characteristic, tense forming, negativity and question making